A method for preparing high entropy alloy-carbon composite microwave absorbing material
Through the preparation method of high-entropy alloy-carbon composite absorbing materials, microwave heating technology is used to prepare absorbing materials with foam-like porous structure, which solves the impedance mismatch problem caused by high-entropy alloy materials due to high density, and achieves efficient and economical absorbing performance, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202410497975.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-04-24
AI Technical Summary
The existing high entropy alloy materials have impedance mismatch due to high density, and the existing preparation methods are complex in processes and long periods, making it difficult to be suitable for applications as absorbing materials.
Using the preparation method of high-entropy alloy-carbon composite absorbing material, absorbent material with a foam-like porous structure is prepared by mixing high-entropy alloy raw materials, carbon materials and diethylene glycol in a specific proportion, grinding agate crucible, insulation of quartz crucibles and microwave heating.
The lightweight wave absorption performance of high-entropy alloy materials is achieved. Through the synergistic effect of foam structure and carbon composite, the controllability and comprehensive wave absorption performance are improved. The preparation process is simple and the energy consumption is low, which is suitable for large-scale production.
Smart Images

Figure CN118406924B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a wave absorbing material. Background Art
[0002] The development of human society is in the electronic information age, and all kinds of electronic and electrical equipment are flooding people's lives. The discovery and use of electromagnetic waves have brought great convenience to production and life, but also interfered with the normal operation of electronic equipment. Not only that, excessive electromagnetic wave energy can also have a negative impact on human health. Microwave absorbing materials are now widely used in aerospace, military and civilian fields. In order to avoid the adverse effects of using electronic and electrical equipment, the research and design of effective electromagnetic wave absorbing materials has become one of the important research hotspots.
[0003] Only alloys of iron, cobalt and nickel have strong ferromagnetic resonance characteristics, which easily lead to impedance mismatch. The displacement of domain walls in the alloy will lead to a narrow absorption bandwidth, which in turn will reduce its absorbing performance. High entropy alloys (HEAs) have attracted extensive attention in electromagnetic wave absorption due to their effective synergy between multiple components and tunable electronic structure. However, the high density and limited chemical stability of HEAs hinder their development as lightweight absorbers.
[0004] Talha Abid et al. prepared porous CoCrFeNiMn foam by adding copper to high entropy alloys through arc melting and then removing copper through an electrochemical dealloying process. The selective phase dissolution method is a simple synthetic technique for preparing nanoporous metals or alloys. It selectively removes unstable components while retaining more stable phases or components. CoCrFeNiMn foam materials can be prepared by inserting copper into basic HEA and removing copper through an electrochemical dealloying process. Xun Cao used template replication technology to prepare porous CrMnFeCoNi high entropy alloy (HEA) foam with a porosity of >95%. Jiangsu Weirui Advanced Materials Technology Co., Ltd. mixed Cr, Mn, Fe, Co, and Ni metal powders in agate mortar, ground them into fine powder, and then used them as raw material powders. Polyvinyl alcohol butyral (PVB) and stearic acid (C18H36O2, 95%) were used as binders and dispersants, respectively. Stearic acid was dissolved in ethanol at 40°C to obtain a clear solution, and CrMnFeCoNi raw material powders were added and ball milled for 5 hours; PVB was then added to the mixture and ball milled for another 19 hours. The sacrificial template used a polyurethane (PU) foam cube with a pore density of 60 holes / inch. The PU foam cube was immersed in the slurry and repeatedly compressed and relaxed. The foam coated with the slurry was dried in the atmosphere for 24 hours and heat treated in an Ar atmosphere using a tubular furnace. Therefore, the existing preparation methods of high entropy alloy foams have the problems of high preparation process requirements, cumbersome preparation processes, long cycles, and the blocky high entropy alloy material has a large density and impedance mismatch, which makes it unsuitable for use as an absorbing material. Summary of the invention
[0005] In order to solve the problem that the existing high entropy alloy materials used as absorbing materials have impedance mismatch due to their high density, and the existing high entropy alloy foam preparation method has the problems of high preparation process requirements, complicated preparation process and long cycle, the present invention provides a method for preparing a high entropy alloy-carbon composite absorbing material.
[0006] The preparation method of the high entropy alloy-carbon composite absorbing material of the present invention is carried out according to the following steps:
[0007] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0008] The raw material of the high entropy alloy is a nitrate, sulfate or oxide of a high entropy alloy element;
[0009] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is: (1-6): (1-6): (1-6): 1:1;
[0010] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is (10-50):1:(1-10);
[0011] The carbon material is carbon nanofiber, graphene oxide or graphene nanosheet;
[0012] The carbon nanofibers have a diameter of 200-600 nm and a length of 5-50 μm;
[0013] The average sheet diameter of the graphene oxide is 2-4 μm, and the average thickness is 2-4 nm;
[0014] The average sheet diameter of the graphene nanosheets is 2-4 μm, and the average thickness is 2-4 nm;
[0015] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0016] The grinding time is 10-60min;
[0017] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0018] The temperature of the heat preservation in the oven is 30-100°C;
[0019] The time of keeping warm in the oven is 0.5-12h;
[0020] Step 4: After the step 3 is kept warm, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy-carbon composite absorbing material; the microwave heating time is 5-120s, and the microwave power is 500-700W.
[0021] The principles and beneficial effects of the present invention are:
[0022] 1. The present invention uses microwave heating to quickly heat up to a higher temperature in a short time. Under microwave heating, the metal salt quickly decomposes to produce gas, which makes the volume of the mixed precursor expand by more than ten times. The gas creates a large number of bubbles in the process, so that the final product has a foam-like porous structure, which solves the problem of impedance mismatch caused by the high density of high entropy alloy materials used as absorbing materials. The large number of pores in the foam structure can be used as a path for the incident electromagnetic wave to propagate, which is conducive to the incident electromagnetic wave entering the absorber and dissipating energy by multiple reflections. In addition, the magnetic properties inherent to the high entropy alloy elements contribute to the magnetic loss mechanism, which plays an important role in the composite absorbing material. The controllable design of the absorbing performance can be achieved by regulating its magnetic properties. In addition to constructing a foam structure, compounding with carbon can also reduce the density of the composite material to a certain extent and contribute to part of the dielectric loss mechanism. The present invention reveals a new viewpoint on the synergistic effect of structure and composition on electromagnetic wave absorption behavior, and opens up a new way to prepare lightweight, high-performance high-entropy alloy-carbon composite electromagnetic wave absorbers.
[0023] 2. The maximum reflection loss value of the 2 mm thick coating prepared from the high entropy alloy-carbon composite absorbing material and paraffin mixture of the present invention reaches -41.30 dB, and the effective absorbing bandwidth is mainly distributed in the Ku band, which proves its excellent comprehensive absorbing performance.
[0024] 3. The present invention only requires microwave heating, and does not require atmosphere protection during the process. The preparation process has low energy consumption, low cost, and simple operation. It does not require complex equipment and is low in cost, which is conducive to large-scale production.
[0025] 4. In the present invention, the FeCoNiCrAl high entropy alloy is respectively compounded with GO, CNF or GNs to prepare the absorbing material. The five metal salts are directly compounded with the carbon material in a one-step method. GO, CNF or GNs all have rich defects and functional groups. The defects and functional groups can effectively absorb microwaves, promote the microwave reaction to quickly reach extremely high temperatures, thereby realizing the preparation of high entropy alloys. At the same time, the present invention controls a shorter reaction time during the reaction process, reduces the consumption of defects and functional groups, and makes the prepared composite material have better absorbing performance and realizes the adjustment of absorbing performance. In the present invention, the carbon material does not exist as a model substrate, but is directly mixed with the metal salt and foamed and expanded into a porous foam structure during microwave heating. During the microwave reaction and under non-argon protection conditions, a small amount of spinel oxide corresponding to the metal will be generated, which can greatly increase the number of heterogeneous interfaces and have a beneficial effect on the absorbing performance.
[0026] 5. The high entropy alloy and carbon in the present invention are combined to broaden the effective absorbing bandwidth and reduce the overall density without sacrificing the absorbing intensity.
[0027] Another method for preparing a high entropy alloy-carbon composite absorbing material of the present invention is carried out according to the following steps:
[0028] The preparation method of the high entropy alloy-carbon composite absorbing material of the present invention is carried out according to the following steps:
[0029] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0030] The raw material of the high entropy alloy is a nitrate, sulfate or oxide of a high entropy alloy element;
[0031] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is: (1-6): (1-6): (1-6): 1:1;
[0032] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is (10-50):1:(1-10);
[0033] The carbon material is carbon nanofiber, graphene oxide or graphene nanosheet;
[0034] The carbon nanofibers have a diameter of 200-600 nm and a length of 5-50 μm;
[0035] The average sheet diameter of the graphene oxide is 2-4 μm, and the average thickness is 2-4 nm;
[0036] The average sheet diameter of the graphene nanosheets is 2-4 μm, and the average thickness is 2-4 nm;
[0037] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0038] The grinding time is 10-60min;
[0039] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0040] The temperature of the heat preservation in the oven is 30-100°C;
[0041] The time of keeping warm in the oven is 0.5-12h;
[0042] Step 4: After the heat preservation in step 3, the quartz crucible is transferred to a muffle furnace for heating to obtain a high entropy alloy-carbon composite absorbing material;
[0043] The heating process is: heating to 300-1000°C at a rate of 2-10°C / min and keeping the temperature for 30min-12h.
[0044] The principles and beneficial effects of the present invention are:
[0045] 1. The present invention adopts muffle furnace heating, which can make the metal salt decompose at high temperature to produce gas, so that the volume of the mixed precursor expands by dozens of times at most. The gas creates a large number of bubbles in the process, so that the final product has a foam-like porous structure. The large number of pores in the foam structure can be used as a path for the incident electromagnetic wave to propagate, which is conducive to the incident electromagnetic wave entering the absorber and propagating multiple times to dissipate energy. In addition, the intrinsic magnetic properties of transition metal elements such as Fe, Co, and Ni contribute to the magnetic loss mechanism, which plays an important role in composite absorbing materials.
[0046] 2. The present invention introduces chromium and aluminum to enhance the corrosion resistance of high entropy alloys. The Al content will have a significant effect on the crystal structure evolution of high entropy alloy nanoparticles. The addition of Al will form an m3al type ordered L12 phase, which improves corrosion resistance. The magnetic properties of high entropy alloys will change with different compositions, so the contribution of magnetic loss will also be different. Therefore, it is possible to adjust the impedance matching of high entropy alloys and achieve regulation of wave absorption performance. High entropy alloys have a relatively stable structure and a dual loss mechanism of dielectric loss and magnetic loss. Compounding high entropy alloys with CNF can improve the comprehensive wave absorption performance of composite materials.
[0047] 4. In the present invention, a large number of pores are generated due to the decomposition and expansion of the mixture of metal salt and DEG during the heating process of the muffle furnace. The porous foam structure finally formed greatly reduces the density of the product. CNF is used as the carbon material matrix, and the short carbon nanofibers are staggered and stacked to easily cross-connect to form a three-dimensional structure. In particular, the obvious expansion of the volume during the high-temperature decomposition of the metal salt will promote the establishment of a three-dimensional network. High-entropy alloy particles can grow with the help of the head and tail of the short carbon nanofibers and the points of cross-stacking. The metal and its oxide particles generated after the decomposition of the metal salt, a large number of heterogeneous interfaces and defects as polarization centers and dipoles provide a large number of interface polarization and dipole polarization mechanisms, contributing to dielectric loss.
[0048] 5. The maximum reflection loss value of the 2 mm thick coating prepared from the FeCoNiCrAl / CNF absorbing material of the present invention and a mixture of paraffin reaches -44.23 dB, and the effective absorption bandwidth less than -10 dB reaches 4.845 GHz. Its effective absorption bandwidth has significant advantages, proving its excellent comprehensive absorption performance.
[0049] 6. The FeCoNiCrAl / CNF product can be obtained by heating in a muffle furnace. Compared with other common methods for preparing high entropy alloys, this method has obvious advantages of short time and high efficiency, which is unmatched by preparation methods using other equipment. The preparation process has low energy consumption, low cost, simple operation, no need for complex equipment, low cost, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a reflection loss diagram of the FeCoNiCrAl-GO composite absorbing material prepared in Example 1 of the present invention;
[0051] Figure 2 This is a reflection loss diagram of the FeCoNiCrAl-CNF composite absorbing material prepared in Example 2 of the present invention;
[0052] Figure 3 This is a reflection loss diagram of the FeCoNiCrAl / CNF composite absorber prepared in Example 3;
[0053] Figure 4 This is a reflection loss diagram of the FeCoNiCrAl / CNF composite absorber prepared in Example 4;
[0054] Figure 5 This is a SEM image of the FeCoNiCrAl / CNF composite absorbing material prepared in Example 4;
[0055] Figure 6 This is a reflection loss diagram of the FeCoNiCrAl / CNF composite absorber prepared in Example 5;
[0056] Figure 7 This is the SEM image of the FeCoNiCrAl / CNF composite absorbing material prepared in Example 5. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0058] Specific implementation method 1: The preparation method of the high entropy alloy-carbon composite absorbing material in this implementation method is carried out according to the following steps:
[0059] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0060] The raw material of the high entropy alloy is a nitrate, sulfate or oxide of a high entropy alloy element;
[0061] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is: (1-6): (1-6): (1-6): 1:1;
[0062] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is (10-50):1:(1-10);
[0063] The carbon material is carbon nanofiber, graphene oxide or graphene nanosheet;
[0064] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0065] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0066] The temperature of the heat preservation in the oven is 30-100°C;
[0067] The time of keeping warm in the oven is 0.5-12h;
[0068] Step 4: After the step 3 is kept warm, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy-carbon composite absorbing material; the microwave heating time is 5-120s, and the microwave power is 500-700W.
[0069] This embodiment has the following beneficial effects:
[0070] 1. This embodiment adopts the characteristic that microwave heating can quickly heat up to a higher temperature in a short time. Under microwave heating, the metal salt quickly decomposes to produce gas, so that the volume of the mixed precursor expands by more than ten times. The gas creates a large number of bubbles in the process, so that the final product has a foam-like porous structure, which solves the problem of impedance mismatch caused by the high density of high entropy alloy materials used as absorbing materials. The large number of pores in the foam structure can be used as a path for the incident electromagnetic wave to propagate, which is conducive to the incident electromagnetic wave entering the absorber and dissipating energy by multiple reflections. In addition, the magnetic properties inherent to the high entropy alloy elements contribute to the magnetic loss mechanism, which plays an important role in composite absorbing materials. By regulating its magnetic properties, the controllable design of absorbing performance can be achieved. In addition to constructing a foam structure, composite with carbon can also reduce the density of the composite material to a certain extent and contribute to part of the dielectric loss mechanism. This embodiment reveals a new viewpoint on the synergistic effect of structure and composition on electromagnetic wave absorption behavior, and opens up a new way to prepare lightweight, high-performance high-entropy alloy-carbon composite electromagnetic wave absorbers.
[0071] 2. The maximum reflection loss value of the 2 mm thick coating prepared from the high entropy alloy-carbon composite absorbing material and paraffin mixture of this embodiment reaches -41.30 dB, and the effective absorbing bandwidth is mainly distributed in the Ku band, which proves its excellent comprehensive absorbing performance.
[0072] 3. This embodiment only requires microwave heating, and no atmosphere protection is required during the process. The preparation process has low energy consumption, low cost, and simple operation. It does not require complex equipment and is low in cost, which is conducive to large-scale production.
[0073] 4. In this embodiment, the FeCoNiCrAl high entropy alloy is respectively compounded with GO, CNF or GNs to prepare the absorbing material. It is a one-step method to directly compound the five metal salts with the carbon material. GO, CNF or GNs all have rich defects and functional groups. The defects and functional groups can effectively absorb microwaves, promote the microwave reaction to quickly reach extremely high temperatures, thereby realizing the preparation of high entropy alloys. At the same time, this embodiment controls a shorter reaction time during the reaction process, reduces the consumption of defects and functional groups, so that the prepared composite material has better absorbing performance and realizes the adjustment of absorbing performance. In this embodiment, the carbon material does not exist as a model substrate, but is directly mixed with the metal salt and foamed and expanded into a porous foam structure during microwave heating. During the microwave reaction and under non-argon protection conditions, a small amount of spinel oxide corresponding to the metal will be generated, which can greatly increase the number of heterogeneous interfaces and have a beneficial effect on the absorbing performance.
[0074] 5. In this embodiment, the high entropy alloy and carbon are combined to broaden the effective absorbing bandwidth and reduce the overall density without sacrificing the absorbing intensity.
[0075] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the diameter of the carbon nanofibers in step 1 is 200-600 nm, and the length is 5-50 μm.
[0076] Specific implementation method three: This implementation method is different from specific implementation method one in that: the average sheet diameter of the graphene oxide in step one is 2-4 μm, and the average thickness is 2-4 nm.
[0077] Specific implementation method 4: This implementation method is different from specific implementation method 1 in that: in step 1, the average sheet diameter of the graphene nanosheets is 2-4 μm, and the average thickness is 2-4 nm.
[0078] Specific implementation method 5: This implementation method is different from specific implementation method 1 in that the grinding time in step 2 is 10-60 minutes.
[0079] Specific embodiment 6: The preparation method of the high entropy alloy-carbon composite absorbing material in this embodiment is carried out according to the following steps:
[0080] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0081] The raw material of the high entropy alloy is a nitrate, sulfate or oxide of a high entropy alloy element;
[0082] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is: (1-6): (1-6): (1-6): 1:1;
[0083] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is (10-50):1:(1-10);
[0084] The carbon material is carbon nanofiber, graphene oxide or graphene nanosheet;
[0085] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0086] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0087] The temperature of the heat preservation in the oven is 30-100°C;
[0088] The time of keeping warm in the oven is 0.5-12h;
[0089] Step 4: After the heat preservation in step 3, the quartz crucible is transferred to a muffle furnace for heating to obtain a high entropy alloy-carbon composite absorbing material;
[0090] The heating process is: heating to 300-1000°C at a rate of 2-10°C / min and keeping the temperature for 30min-12h.
[0091] 1. This embodiment adopts muffle furnace heating, which can make the metal salt decompose at high temperature to produce gas, so that the volume of the mixed precursor expands by dozens of times at most. The gas creates a large number of bubbles in the process, so that the final product has a foam-like porous structure. A large number of pores in the foam structure can be used as a path for the incident electromagnetic wave to propagate, which is conducive to the incident electromagnetic wave entering the absorber and propagating multiple times to dissipate energy. In addition, the intrinsic magnetic properties of transition metal elements such as Fe, Co, and Ni contribute to the magnetic loss mechanism, which plays an important role in composite absorbing materials.
[0092] 2. This embodiment introduces chromium and aluminum to enhance the corrosion resistance of high entropy alloys. The Al content will have a significant effect on the crystal structure evolution of high entropy alloy nanoparticles. The addition of Al will form an m3al type ordered L12 phase, which improves corrosion resistance. The magnetic properties of high entropy alloys will change with different compositions, so the contribution of magnetic loss will also be different. Therefore, it is possible to adjust the impedance matching of high entropy alloys and achieve regulation of wave absorption performance. High entropy alloys have a relatively stable structure and a dual loss mechanism of dielectric loss and magnetic loss. Compounding high entropy alloys with CNF can improve the comprehensive wave absorption performance of composite materials.
[0093] 4. In this embodiment, a large number of pores are generated due to the decomposition and expansion of the mixture of metal salt and DEG during the heating process of the muffle furnace. The porous foam structure finally formed greatly reduces the density of the product. CNF is used as the carbon material matrix, and the staggered stacking of short carbon nanofibers is easy to cross-connect to form a three-dimensional structure. In particular, the obvious expansion of the volume during the high-temperature decomposition of the metal salt will promote the establishment of a three-dimensional network. High-entropy alloy particles can grow with the help of the head and tail of the short carbon nanofibers and the points of cross-stacking. The metal and its oxide particles produced after the decomposition of the metal salt, a large number of heterogeneous interfaces and defects as polarization centers and dipoles provide a large number of interface polarization and dipole polarization mechanisms, contributing to dielectric loss.
[0094] 5. The maximum reflection loss value of the 2 mm thick coating prepared from the FeCoNiCrAl / CNF absorbing material and paraffin mixture of this embodiment reaches -44.23 dB, and the effective absorption bandwidth less than -10 dB reaches 4.845 GHz. Its effective absorption bandwidth has significant advantages, proving its excellent comprehensive absorbing performance.
[0095] 6. The FeCoNiCrAl / CNF product can be obtained by heating in a muffle furnace. Compared with other common methods for preparing high entropy alloys, this method has obvious advantages of short time and high efficiency, which is unmatched by other equipment preparation methods. The preparation process has low energy consumption, low cost, simple operation, no need for complex equipment, low cost, and is conducive to large-scale production.
[0096] Specific implementation method 7: This implementation method is different from specific implementation method 6 in that: the diameter of the carbon nanofibers in step 1 is 200-600 nm, and the length is 5-50 μm.
[0097] Specific implementation eight: This implementation differs from specific implementation six in that: in step one, the average sheet diameter of the graphene oxide is 2-4 μm, and the average thickness is 2-4 nm.
[0098] Specific embodiment nine: This embodiment differs from specific embodiment six in that: in step one, the average sheet diameter of the graphene nanosheets is 2-4 μm, and the average thickness is 2-4 nm.
[0099] Specific implementation method ten: This implementation method is different from specific implementation method six in that: the grinding time in step two is 10-60 minutes.
[0100] Example 1
[0101] The preparation method of the high entropy alloy-carbon composite absorbing material of this embodiment is carried out according to the following steps:
[0102] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0103] The raw material of the high entropy alloy is nitrate of high entropy alloy element;
[0104] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is 1:1:1:1:1;
[0105] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is 20:1:5;
[0106] The carbon material is graphene oxide;
[0107] The average sheet diameter of the graphene oxide is 3 μm and the average thickness is 3 nm;
[0108] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0109] The grinding time is 30 min;
[0110] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0111] The temperature of the heat preservation in the oven is 80°C;
[0112] The time of keeping warm in the oven is 8 hours;
[0113] Step 4: After the step 3 is kept warm, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy-carbon composite absorbing material; the microwave heating time is 60s, and the microwave power is 700W.
[0114] The obtained FeCoNiCrAl-GO composite absorber was mixed with paraffin wax at a mass ratio of 1:1 and pressed into a ring and its electromagnetic parameters were tested using a vector network instrument; Figure 1 This is the reflection loss diagram of the FeCoNiCrAl-GO composite absorbing material prepared in Example 1 of the present invention. Figure 1 It can be seen that the reflection loss value of the absorber can reach about -41.30dB, the effective absorption bandwidth is mainly distributed in the Ku band, and the C band also has certain absorption performance. It is expected that the absorption performance can be regulated by adjusting the amount of GO added.
[0115] Example 2
[0116] The preparation method of the high entropy alloy-carbon composite absorbing material of this embodiment is carried out according to the following steps:
[0117] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0118] The raw material of the high entropy alloy is nitrate of high entropy alloy element;
[0119] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is 1:1:1:1:1;
[0120] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is 20:1:10;
[0121] The carbon material is carbon nanofiber;
[0122] The carbon nanofibers have a diameter of 200-600 nm and a length of 5-50 μm;
[0123] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0124] The grinding time is 30 min;
[0125] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0126] The temperature of the heat preservation in the oven is 80°C;
[0127] The time of keeping warm in the oven is 2h;
[0128] Step 4: After the step 3 is kept warm, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy-carbon composite absorbing material; the microwave heating time is 60s, and the microwave power is 700W.
[0129] The obtained FeCoNiCrAl-CNF composite absorber was mixed with paraffin wax at a mass ratio of 1:1 and pressed into a ring and its electromagnetic parameters were tested using a vector network instrument; Figure 2 This is the reflection loss diagram of the FeCoNiCrAl-CNF composite absorber prepared in Example 2. Figure 2 It can be seen that the reflection loss value of the absorber can reach about -37.31dB, and the effective absorption bandwidth is also mainly distributed in the Ku band. In addition, it also has good absorption performance in the C band. The nitrogen adsorption and desorption test results show that the BET specific surface area of the FeCoNiCrAl-CNF composite absorber is 69.4063m 2 / g, and the average pore size is 4.1303nm.
[0130] Example 3
[0131] The preparation method of the high entropy alloy-carbon composite absorbing material of this embodiment is carried out according to the following steps:
[0132] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0133] The raw material of the high entropy alloy is nitrate of high entropy alloy element;
[0134] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is 1:1:1:1:1;
[0135] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is 45:1:5;
[0136] The carbon material is carbon nanofiber;
[0137] The carbon nanofibers have a diameter of 200-600 nm and a length of 5-50 μm;
[0138] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0139] The grinding time is 30 min;
[0140] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0141] The temperature of the heat preservation in the oven is 80°C;
[0142] The time of keeping warm in the oven is 1h;
[0143] Step 4: After the heat preservation in step 3, the quartz crucible is transferred to a muffle furnace for heating to obtain a high entropy alloy-carbon composite absorbing material;
[0144] The heating process is: heating to 800° C. at a rate of 5° C. / min and keeping the temperature for 1 hour.
[0145] The obtained FeCoNiCrAl / CNF composite absorber was mixed with paraffin wax at a mass ratio of 1:1 and pressed into a ring and its electromagnetic parameters were tested using a vector network instrument; Figure 3 This is the reflection loss diagram of the FeCoNiCrAl / CNF absorbing material prepared in Example 3. Figure 3 It can be seen that the reflection loss value of the absorber can reach about -14dB, and the effective absorption bandwidth is mainly distributed near the C band, which can be used for electromagnetic wave absorption in the low frequency band.
[0146] Example 4
[0147] The preparation method of the high entropy alloy-carbon composite absorbing material of this embodiment is carried out according to the following steps:
[0148] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0149] The raw material of the high entropy alloy is nitrate of high entropy alloy element;
[0150] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is 1:1:1:1:1;
[0151] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is 40:1:8;
[0152] The carbon material is carbon nanofiber;
[0153] The carbon nanofibers have a diameter of 200-600 nm and a length of 5-50 μm;
[0154] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0155] The grinding time is 30 min;
[0156] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0157] The temperature of the heat preservation in the oven is 80°C;
[0158] The time of keeping warm in the oven is 5 hours;
[0159] Step 4: After the heat preservation in step 3, the quartz crucible is transferred to a muffle furnace for heating to obtain a high entropy alloy-carbon composite absorbing material;
[0160] The heating process is: heating to 1000° C. at a rate of 5° C. / min and keeping the temperature for 1 hour.
[0161] The obtained FeCoNiCrAl / CNF composite absorber was mixed with paraffin wax at a mass ratio of 1:1 and pressed into a ring and its electromagnetic parameters were tested using a vector network instrument; Figure 3 This is the reflection loss diagram of the FeCoNiCrAl / CNF absorbing material prepared in Example 4. Figure 3 It can be seen that the reflection loss value of the absorber is only about -5.6dB, which has certain absorbing performance, but the absorbing performance needs to be further optimized. The reason may be that the temperature of the muffle furnace is too high, causing the porous foam structure to collapse. Figure 5 This is a SEM image of the FeCoNiCrAl / CNF composite absorbing material prepared in Example 4. From the image, it can be found that the particles are densely packed and there are very few holes, which is not conducive to obtaining good absorbing performance.
[0162] Example 5
[0163] The preparation method of the high entropy alloy-carbon composite absorbing material of this embodiment is carried out according to the following steps:
[0164] Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol;
[0165] The raw material of the high entropy alloy is nitrate of high entropy alloy element;
[0166] The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is 1:1:1:1:1;
[0167] The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is 30:1:5;
[0168] The carbon material is carbon nanofiber;
[0169] The carbon nanofibers have a diameter of 200-600 nm and a length of 5-50 μm;
[0170] Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product;
[0171] The grinding time is 30 min;
[0172] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time;
[0173] The temperature of the heat preservation in the oven is 80°C;
[0174] The time of keeping warm in the oven is 0.5h;
[0175] Step 4: After the heat preservation in step 3, the quartz crucible is transferred to a muffle furnace for heating to obtain a high entropy alloy-carbon composite absorbing material;
[0176] The heating process is: heating to 400° C. at a rate of 5° C. / min and keeping the temperature for 1 hour.
[0177] The obtained FeCoNiCrAl / CNF composite absorber was mixed with paraffin wax at a mass ratio of 1:1 and pressed into a ring and its electromagnetic parameters were tested using a vector network instrument; Figure 6 This is the reflection loss diagram of the FeCoNiCrAl / CNF absorbing material prepared in Example 5. Figure 6It can be seen that the reflection loss value of the absorber can reach about -20 dB, and the effective absorption bandwidth is mainly located in the Ku band. Compared with Example 3 and Example 4, the effective absorption band changes significantly. This shows that with the change of the heating temperature of the muffle furnace, the absorption performance and action band of the FeCoNiCrAl / CNF system also change accordingly, and the design of the absorption performance of the target product can be achieved by regulating the heating temperature of the muffle furnace. Figure 7 This is the SEM image of the FeCoNiCrAl / CNF composite absorbing material prepared in Example 5. From the image, it can be observed that the short carbon nanofibers are intertwined to form a three-dimensional structure, and the high entropy alloy particles grow at the fiber heads and tails and at the interlaced parts to form a three-dimensional chain structure.
Claims
1. A method for preparing a high entropy alloy-carbon composite absorbing material, characterized in that: The preparation method of the high entropy alloy-carbon composite absorbing material is carried out according to the following steps: Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol; The raw material of the high entropy alloy is a nitrate, sulfate or oxide of a high entropy alloy element; The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is: (1-6): (1-6): (1-6): 1:1; The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is (10-50):1:(1-10); The carbon material is carbon nanofiber; Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product; Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time; The temperature of the heat preservation in the oven is 30-100°C; The time of keeping warm in the oven is 0.5-12h; Step 4: After the step 3 is kept warm, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy-carbon composite absorbing material; the microwave heating time is 5-120s, and the microwave power is 500-700W.
2. The method for preparing the entropy alloy-carbon composite absorbing material according to claim 1, characterized in that: In step 1, the carbon nanofibers have a diameter of 200-600 nm and a length of 5-50 μm.
3. The method for preparing the entropy alloy-carbon composite absorbing material according to claim 1, characterized in that: The grinding time in step 2 is 10-60 min.
4. A method for preparing a high entropy alloy-carbon composite absorbing material, characterized in that: The preparation method of the high entropy alloy-carbon composite absorbing material is carried out according to the following steps: Step 1: Weigh the raw materials of high entropy alloy, carbon material and diethylene glycol; The raw material of the high entropy alloy is a nitrate, sulfate or oxide of a high entropy alloy element; The high entropy alloy is FeCoNiCrAl, and the molar ratio of Fe, Co, Ni, Cr and Al is: (1-6): (1-6): (1-6): 1:1; The mass ratio of the raw material of the high entropy alloy, the carbon material and diethylene glycol is (10-50):1:(1-10); The carbon material is carbon nanofiber, graphene oxide or graphene nanosheet; Step 2: Put the raw materials of high entropy alloy, carbon material and diethylene glycol weighed in step 1 into an agate crucible and grind them evenly to obtain a paste product; Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in an oven for a period of time; The temperature of the heat preservation in the oven is 30-100°C; The time of keeping warm in the oven is 0.5-12h; Step 4: After the heat preservation in step 3, the quartz crucible is transferred to a muffle furnace for heating to obtain a high entropy alloy-carbon composite absorbing material; The heating process is: heating to 300-1000°C at a rate of 2-10°C / min and keeping the temperature for 30min-12h.
5. The method for preparing the entropy alloy-carbon composite absorbing material according to claim 4, characterized in that: The graphene nanosheets in step 1 have an average sheet diameter of 2-4 μm and an average thickness of 2-4 nm.
6. The method for preparing the entropy alloy-carbon composite absorbing material according to claim 4, characterized in that: The grinding time in step 2 is 10-60 min.
Citation Information
Patent Citations
Solvent-free type three-dimensional metal nanofoam and preparation method thereof
CN106498217A
High-entropy alloy / graphene composite material with wave-absorbing property and preparation method of high-entropy alloy / graphene composite material
CN115161531A
Three-dimensional intercommunicated reticular heat-conducting and wave-absorbing foam material as well as preparation method and application thereof
CN116333684A